Preparation method and application of porous carbon with high specific surface area and high conductivity
By imidazole cross-linking modification and high-temperature pyrolysis treatment on alkali lignin, a high specific surface area and high conductivity porous carbon is formed, and the specific capacitance is improved by uniform adsorption of permanganate, the problem of insufficient performance of porous carbon materials in the prior art is solved, and a high-performance supercapacitor electrode material is realized.
Patent Information
- Application Number
- CN202411936944.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art is difficult to provide porous carbon materials with high specific surface area, high conductivity, and high specific capacitance for supercapacitors.
The modified alkali lignin with a microporous crosslinking network is formed by adding 1,4-bis[(imidazole-4-formyl chloride)methyl]benzene to the alkali lignin, and a high specific surface area, highly conductive porous carbon is formed by high temperature pyrolysis and water vapor activation, while uniformly adsorbing and loading of permanganate to improve the specific capacitance.
The high pore volume and specific surface area of porous carbon are achieved, the agglomeration of manganese oxides is inhibited, the actual specific capacitance is improved, and the electrochemical cycle stability is enhanced.
Smart Images

Figure BDA0005211725650000021 
Figure BDA0005211725650000031 
Figure BDA0005211725650000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of supercapacitors, and in particular to a preparation method and application of porous carbon with high specific surface area and high conductivity. Background Art
[0002] Supercapacitor is a new type of energy storage device with the characteristics of fast charging and discharging, high power density, long cycle life, and excellent energy storage characteristics. The electrode material plays a decisive role in the electrochemical performance of supercapacitors. The current electrode materials mainly include activated carbon, transition metal oxides, transition metal sulfides, conductive polymers, etc. Among them, porous activated carbon has a large specific surface area, good conductivity, stable chemical properties, and a variety of preparation methods, making it an ideal electrode material.
[0003] Common activated carbon uses biomass resources such as fruit shells, straw, lignin, starch, etc. as carbon precursors. After high-temperature carbonization and activation pore formation, activated carbon materials with higher specific surface area can be obtained. At the same time, activated carbon is doped with heteroatoms such as nitrogen and sulfur to improve the electrochemical properties of activated carbon, such as conductivity. And using activated carbon as a carrier to load transition metal oxides, etc., can improve its actual specific capacitance. Patent CN112820550B discloses a manganese dioxide composite nitrogen-sulfur dual-doped porous carbon and its preparation method and application. It uses thiourea, sodium alginate, potassium nitrate, potassium permanganate, etc. as raw materials, and simultaneously realizes the regulation of the pore structure of porous carbon and the manganese dioxide content. The obtained porous carbon composite material is used as an electrode material for supercapacitors and exhibits good electrochemical properties. Summary of the invention
[0004] The technical problem solved by the present invention is to provide a porous carbon with high specific surface area, high conductivity and high specific capacitance for use in supercapacitors.
[0005] Technical solution: A method for preparing porous carbon with high specific surface area and high conductivity:
[0006] Step A: Add N,N-dimethylformamide and alkali lignin into a flask, stir, add 1,4-di[(imidazole-4-carbonyl chloride)methyl]benzene and triethylamine, stir and react at 70-90° C. for 12-24 hours, cool, filter, wash with water and ethanol in turn, and dry to obtain imidazole cross-linked modified alkali lignin.
[0007] Step B, adding a potassium permanganate aqueous solution with a mass concentration of (3-20) g / L into a flask, imidazole cross-linked modified alkali lignin, and ultrasonically treating it for 2-4 hours in an ultrasonic instrument at a frequency of 20-30 kHz. After filtering, the modified alkali lignin is dried, placed in an atmosphere furnace, nitrogen is introduced, the temperature is raised to 550-700° C., and pyrolysis treatment is performed for 1.5-2 hours; then water vapor is introduced at a flow rate of 0.3-0.6 mL / L, the temperature is raised to 800-900° C., and activation treatment is performed for 1-1.5 hours; the introduction of water vapor is stopped, and the mixture is cooled to room temperature to obtain a porous carbon with high specific surface area and high conductivity.
[0008] Furthermore, in step A, the masses of 1,4-bis[(imidazole-4-carbonyl chloride)methyl]benzene and triethylamine are 5-30% and 2.8-17% of the mass of alkali lignin, respectively.
[0009] Further, the preparation method of 1,4-bis[(imidazole-4-carbonyl chloride)methyl]benzene is:
[0010] Step (1), add N, N-dimethylformamide and imidazole-4-carboxylic acid methyl ester to a flask, pass nitrogen, add sodium hydride, heat to 80-90°C, react for 1-2h, then add 1, 4-di(bromomethyl)benzene, react for 18-24h, remove N, N-dimethylformamide by distillation under reduced pressure, add the product after washing with water to methanol, add sodium hydroxide solution with a mass concentration of 60-80g / L, heat to 70-85°C, condense and reflux for 5-8h, remove methanol by distillation under reduced pressure, add hydrochloric acid solution to adjust the pH to 4-5, filter, wash the filter cake with water, and obtain 1, 4-di[(imidazole-4-carboxylic acid) methyl] benzene. The reaction formula is:
[0011]
[0012] Step (2), add thionyl chloride and 1,4-di[(imidazole-4-carboxylic acid)methyl]benzene to a flask, introduce nitrogen, heat to 60-70°C, condense and reflux for 3-4h, distill under reduced pressure, and dry to obtain 1,4-di[(imidazole-4-carboxylic acid chloride)methyl]benzene. The reaction formula is:
[0013]
[0014] Furthermore, in step (1), the masses of methyl imidazole-4-carboxylate and sodium hydride are 96-106% and 28-34% of the mass of 1,4-di(bromomethyl)benzene, respectively.
[0015] Furthermore, in step (2), the mass of 1,4-di[(imidazole-4-carboxylic acid)methyl]benzene is 25-35% of the mass of thionyl chloride.
[0016] The technical effect of the present invention is that the present invention utilizes multiple acyl chloride groups of 1,4-di[(imidazole-4-carbonyl chloride)methyl]benzene to react with hydroxyl groups of alkali lignin to cross-link the alkali lignin to form a modified alkali lignin with a microporous cross-linked network, and the modified alkali lignin contains a large amount of imidazole nitrogen-containing heterocyclic rings, which can react with permanganate KMnO4 - Hydrogen bond interactions occur, so that a large amount of KMnO4- is uniformly adsorbed into the lignin matrix. After high-temperature pyrolysis and water vapor activation, the cross-linked alkali lignin is carbonized to form porous carbon, which shows a higher pore volume and specific surface area. KMnO4- is pyrolyzed to generate manganese oxides, which are uniformly loaded into the matrix of the porous carbon. The problem of pore blockage will not occur, and the pore volume and specific surface area of the porous carbon will not be affected. At the same time, the agglomeration of manganese oxides is suppressed, which is conducive to the generation of more pseudocapacitance and the improvement of the actual specific capacitance of the porous carbon.
[0017] The cross-linked modified alkali lignin of the present invention contains a large number of imidazole groups, and high-temperature pyrolysis forms active sites such as pyridine nitrogen and graphite nitrogen, which can improve the conductivity of porous carbon, promote electron transmission, and further improve specific capacitance. In addition, the porous carbon is coated on the outside of manganese oxide, and the manganese oxide is not easy to fall off, and is not easy to expand in volume, and the structural stability is better, so that the porous carbon has better electrochemical cycle stability performance, and after multiple cycles, it still maintains a high specific capacitance. It is an ideal supercapacitor electrode material. DETAILED DESCRIPTION
[0018] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only partial embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] Example 1: Step (1), add 20-30mL N,N-dimethylformamide, 0.48g imidazole-4-carboxylic acid methyl ester into a flask, pass nitrogen, add 0.17g sodium hydride, heat to 85°C, react for 2h, then add 0.5g 1,4-bis(bromomethyl)benzene, react for 18h, remove N,N-dimethylformamide by distillation under reduced pressure, wash the product with water, add methanol, add sodium hydroxide solution with a mass concentration of 80g / L, heat to 70°C, condense and reflux for 6h, remove methanol by distillation under reduced pressure, add hydrochloric acid solution to adjust the pH to 5, filter, wash the filter cake with water, and obtain 1,4-bis[(imidazole-4-carboxylic acid)methyl]benzene.
[0020] Step (2), add 10g of thionyl chloride and 3g of 1,4-bis[(imidazole-4-carboxylic acid)methyl]benzene into a flask, introduce nitrogen, heat to 70°C, condense and reflux for 3h, distill under reduced pressure, and dry to obtain 1,4-bis[(imidazole-4-carboxylic acid)methyl]benzene.
[0021] Step (3), add 150mL N,N-dimethylformamide and 10g alkali lignin into a flask, stir, add 0.5g 1,4-di[(imidazole-4-carbonyl chloride)methyl]benzene and 0.28g triethylamine, stir and react at 80°C for 12h, cool, filter, wash with water and ethanol in turn, and dry to obtain imidazole cross-linked modified alkali lignin.
[0022] Step (4), add 600mL of potassium permanganate aqueous solution with a mass concentration of 3g / L and 20g of imidazole cross-linked modified alkali lignin into a flask, and perform ultrasonic treatment for 4h in an ultrasonic instrument at a frequency of 20kHz. After filtering, the modified alkali lignin is dried, placed in an atmosphere furnace, nitrogen is introduced, the temperature is raised to 600°C, and pyrolysis treatment is performed for 2h; then water vapor is introduced at a flow rate of 0.3mL / L, the temperature is raised to 900°C, and activation treatment is performed for 1h; stop introducing water vapor, cool to room temperature, and obtain a porous carbon with high specific surface area and high conductivity.
[0023] Example 2: Step (1), add 30mL N,N-dimethylformamide, 0.53g imidazole-4-carboxylic acid methyl ester into a flask, pass nitrogen, add 0.16g sodium hydride, heat to 80°C, react for 2h, then add 0.5g 1,4-bis(bromomethyl)benzene, react for 24h, remove N,N-dimethylformamide by distillation under reduced pressure, wash the product with water, add methanol, add sodium hydroxide solution with a mass concentration of 60g / L, heat to 85°C, condense and reflux for 5h, remove methanol by distillation under reduced pressure, add hydrochloric acid solution to adjust the pH to 4-5, filter, wash the filter cake with water to obtain 1,4-bis[(imidazole-4-carboxylic acid)methyl]benzene.
[0024] Step (2), add 10 g of thionyl chloride and 3.5 g of 1,4-bis[(imidazole-4-carboxylic acid)methyl]benzene into a flask, introduce nitrogen, heat to 60° C., condense and reflux for 4 h, distill under reduced pressure, and dry to obtain 1,4-bis[(imidazole-4-carboxylic acid chloride)methyl]benzene.
[0025] Step (3), add 150-500mL N,N-dimethylformamide and 10g alkali lignin into a flask, stir, add 1.8g 1,4-di[(imidazole-4-carbonyl chloride)methyl]benzene and 1.02g triethylamine, stir and react at 90°C for 12h, cool, filter, wash with water and ethanol in turn, and dry to obtain imidazole cross-linked modified alkali lignin.
[0026] Step (4), adding 800 mL of a potassium permanganate aqueous solution with a mass concentration of 10 g / L and 20 g of imidazole cross-linked modified alkali lignin into a flask, and ultrasonically treating the flask at a frequency of 20 kHz for 4 h in an ultrasonic instrument. After filtering, the modified alkali lignin is dried, placed in an atmosphere furnace, nitrogen is introduced, the temperature is raised to 550° C., and pyrolysis treatment is performed for 2 h; then, water vapor is introduced at a flow rate of 0.6 mL / L, the temperature is raised to 800° C., and activation treatment is performed for 1.5 h; the introduction of water vapor is stopped, and the flask is cooled to room temperature to obtain a porous carbon with a high specific surface area and high conductivity.
[0027] Example 3: Step (1), add 20mL N,N-dimethylformamide, 0.48g imidazole-4-carboxylic acid methyl ester into a flask, pass nitrogen, add 0.14g sodium hydride, heat to 90°C, react for 1h, then add 0.5g 1,4-bis(bromomethyl)benzene, react for 24h, remove N,N-dimethylformamide by distillation under reduced pressure, wash the product with water, add methanol, add sodium hydroxide solution with a mass concentration of 60g / L, heat to 80°C, condense and reflux for 8h, remove methanol by distillation under reduced pressure, add hydrochloric acid solution to adjust the pH to 4, filter, wash the filter cake with water, and obtain 1,4-bis[(imidazole-4-carboxylic acid)methyl]benzene.
[0028] Step (2), add 10 g of thionyl chloride and 2.5 g of 1,4-bis[(imidazole-4-carboxylic acid)methyl]benzene into a flask, introduce nitrogen, heat to 70° C., condense and reflux for 3 h, distill under reduced pressure, and dry to obtain 1,4-bis[(imidazole-4-carboxylic acid chloride)methyl]benzene.
[0029] Step (3), add 500 mL of N,N-dimethylformamide and 10 g of alkali lignin into a flask, stir, add 3 g of 1,4-di[(imidazole-4-carbonyl chloride)methyl]benzene and 1.7 g of triethylamine, stir and react at 70° C. for 24 h, cool, filter, wash with water and ethanol in turn, and dry to obtain imidazole cross-linked modified alkali lignin.
[0030] Step (4), adding 800 mL of a potassium permanganate aqueous solution with a mass concentration of 20 g / L and 20 g of imidazole cross-linked modified alkali lignin into a flask, and ultrasonically treating the mixture for 2 h at a frequency of 30 kHz in an ultrasonic instrument. After filtering, the modified alkali lignin is dried, placed in an atmosphere furnace, nitrogen is introduced, the temperature is raised to 700° C., and pyrolysis treatment is performed for 1.5 h; then, water vapor is introduced at a flow rate of 0.4 mL / L, the temperature is raised to 850° C., and activation treatment is performed for 1.5 h; the introduction of water vapor is stopped, and the mixture is cooled to room temperature to obtain a porous carbon with high specific surface area and high conductivity.
[0031] Comparative Example 1: Step (1), placing imidazole cross-linked modified alkali lignin (prepared in the same manner as in Example 1) in an atmosphere furnace, introducing nitrogen, raising the temperature to 600°C, and conducting a pyrolysis treatment for 2 hours; then introducing water vapor at a flow rate of 0.3 mL / L, raising the temperature to 900°C, and conducting an activation treatment for 1 hour; stopping the introduction of water vapor, cooling to room temperature, and obtaining porous carbon.
[0032] Comparative Example 2: Step (1), add 600 mL of potassium permanganate aqueous solution with a mass concentration of 3 g / L and 20 g of alkali lignin into a flask, and perform ultrasonic treatment for 4 h in an ultrasonic instrument at a frequency of 20 kHz. After filtering, the modified alkali lignin is dried, placed in an atmosphere furnace, nitrogen is introduced, the temperature is raised to 600°C, and pyrolysis treatment is performed for 2 h; then water vapor is introduced at a flow rate of 0.3 mL / L, the temperature is raised to 900°C, and activation treatment is performed for 1 h; the introduction of water vapor is stopped, and the mixture is cooled to room temperature to obtain porous carbon.
[0033] Comparative Example 3: Step (1), add 150 mL of N,N-dimethylformamide and 10 g of alkali lignin into a flask, stir, add 0.5 g of terephthaloyl chloride and 0.28 g of triethylamine, stir and react at 80°C for 12 h, cool, filter, wash with water and ethanol in turn, and dry to obtain cross-linked modified alkali lignin.
[0034] Step (2), adding 600 mL of a potassium permanganate aqueous solution with a mass concentration of 3 g / L and 20 g of cross-linked modified alkali lignin into a flask, and ultrasonically treating the flask at a frequency of 20 kHz for 4 h in an ultrasonic instrument. After filtering, the modified alkali lignin is dried, placed in an atmosphere furnace, nitrogen is introduced, the temperature is raised to 600° C., and pyrolysis treatment is performed for 2 h; then, water vapor is introduced at a flow rate of 0.3 mL / L, the temperature is raised to 900° C., and activation treatment is performed for 1 h; the introduction of water vapor is stopped, and the flask is cooled to room temperature to obtain porous carbon.
[0035] Comparative Example 4: Step (1), placing the imidazole cross-linked modified alkali lignin (prepared in the same manner as in Example 1) in an atmosphere furnace, introducing nitrogen, raising the temperature to 600°C, and conducting a pyrolysis treatment for 2 hours; then introducing water vapor at a flow rate of 0.3 mL / L, raising the temperature to 900°C, and conducting an activation treatment for 1 hour; stopping the introduction of water vapor, cooling to room temperature, and obtaining porous carbon.
[0036] Step (2), add 600 mL of a 3 g / L potassium permanganate aqueous solution and 20 g of porous carbon into a flask, perform ultrasonic treatment for 4 h in an ultrasonic instrument at a frequency of 20 kHz, filter and dry the modified alkali lignin, place it in an atmosphere furnace, introduce nitrogen, heat to 600 ° C, and perform pyrolysis treatment for 2 h to obtain manganese oxide-porous carbon.
[0037] The specific surface area and pore volume of the porous carbon were tested by a fully automatic specific surface and porosity analyzer, and nitrogen adsorption and desorption tests were carried out at 77K to draw the adsorption and desorption isotherms.
[0038] Table 1
[0039] <![CDATA[Total pore volume (cm 3 / g)]]> <![CDATA[Specific surface area (m 2 / g)]]> Example 1 1.205 1939.1 Example 2 1.698 2690.2 Example 3 1.315 2129.8 Comparative Example 1 1.210 1964.9 Comparative Example 2 0.613 974.9 Comparative Example 3 1.134 1828.0 Comparative Example 4 0.436 727.7
[0040] It can be seen from Table 1 that the total pore volume of the porous carbons of Examples 1-3 reaches 1.205-1.698 cm 3 / g, with a specific surface area of 1939.1-2690.2m 2 / g, this is because the multiple acyl chloride groups of 1,4-di[(imidazole-4-carbonyl chloride)methyl]benzene react with the hydroxyl groups of alkali lignin to cross-link the alkali lignin to form a modified alkali lignin with a microporous cross-linked network, which is then carbonized at high temperature and activated with water vapor, giving the porous carbon a higher pore volume and specific surface area. At the same time, the manganese oxide generated by pyrolysis grows evenly in the porous carbon matrix, and the problem of pore blockage will not occur, and the pore volume and specific surface area of the porous carbon will not be affected.
[0041] Comparative Examples 1 and 3 respectively use 1,4-di[(imidazole-4-carboxylic acid)methyl]benzene and terephthaloyl chloride to cross-link and modify alkali lignin to form a microporous cross-linked network structure, and then undergo high-temperature carbonization and water vapor activation to obtain porous carbon with very high pore volume and specific surface area.
[0042] The alkali lignin of Comparative Example 2 has not been cross-linked and modified, and no microporous cross-linked network is formed, and the pore volume and specific surface area of the obtained porous carbon are relatively low.
[0043] In Comparative Example 4, porous carbon is used as a carrier to load potassium permanganate, and then potassium permanganate is pyrolyzed to generate manganese oxide. The manganese oxide adheres to the surface and pores of the porous carbon, blocking the pores, resulting in lower pore volume and specific surface area of the porous carbon material.
[0044] Porous carbon (Comparative Example 4 is manganese oxide-porous carbon) and conductive carbon black, polyvinylidene fluoride are added to N, N-dimethylformamide in a mass ratio of 8:1:1, ultrasonically dispersed, and then the slurry is coated on the surface of graphite paper and dried to form a working electrode, with a platinum sheet as a counter electrode, an Ag / AgCl electrode as a reference electrode, and an electrolyte of 6 mol / L KOH solution or 1 mol / L Na2SO4 solution. An electrochemical workstation is used to perform electrochemical performance tests using a three-electrode system.
[0045] Table 2 Specific capacitance test when the electrolyte is 6 mol / L KOH solution
[0046]
[0047]
[0048] Table 3 Specific capacitance test when the electrolyte is 1 mol / L Na2SO4 solution
[0049]
[0050] Table 4 Cyclic stability test at current density of 1A / g
[0051]
[0052] As shown in Tables 2-4, the porous carbon loaded with manganese oxide in Examples 1-3 as the working electrode of the supercapacitor has a very high actual specific capacitance at a current density of 1-5 A / g, and has a very good rate performance. Moreover, after 200 cycles, it still maintains a high specific capacitance and excellent cycle stability. This is because the matrix of the imidazole cross-linked modified alkali lignin contains more imidazole nitrogen-containing heterocyclic rings, which can react with the permanganate KMnO4 - Hydrogen bond interactions occur, and imidazole cross-linked modified alkali lignin has a microporous cross-linked network structure, which can transfer a large amount of KMnO4 - Uniformly adsorbed into the lignin matrix, after high temperature pyrolysis, cross-linked alkali lignin carbonization forms porous carbon, KMnO4 - Manganese oxide is generated and evenly loaded into the matrix of porous carbon, which inhibits the agglomeration of manganese oxide, thereby generating more pseudocapacitance, which is beneficial to improve the actual specific capacitance of porous carbon. In addition, the high-temperature pyrolysis of imidazole groups forms active sites such as pyridine nitrogen and graphite nitrogen, which can improve the conductivity of porous carbon, promote electron transfer, and further improve specific capacitance. The porous carbon is coated on the outside of manganese oxide, and manganese oxide is not easy to fall off, and it is not easy to expand in volume. The structural stability is better, which makes the porous carbon have better electrochemical cycle stability.
[0053] In Comparative Example 1, potassium permanganate was not added, and the obtained porous carbon matrix did not contain manganese oxide, resulting in a lower actual specific capacitance of the porous carbon.
[0054] The alkaline lignin in Comparative Example 2 does not contain imidazole nitrogen-containing heterocycles and microporous cross-linked network structures, making it difficult to effectively and evenly adsorb potassium permanganate into the lignin matrix. The resulting porous carbon matrix contains less manganese oxide, and the manganese oxide has poor dispersion in the porous carbon matrix and is easily agglomerated, resulting in a poor pseudocapacitance effect, resulting in a lower actual specific capacitance of the porous carbon.
[0055] The cross-linked modified alkali lignin of Comparative Example 3 does not contain imidazole groups and is -The interaction force is weak, making it difficult to effectively and evenly adsorb potassium permanganate into the lignin matrix. In addition, after high-temperature carbonization, the porous carbon matrix does not contain active sites such as pyridinic nitrogen and graphitic nitrogen, resulting in a low actual specific capacitance of the porous carbon.
[0056] Comparative Example 4 uses porous carbon as a carrier to load potassium permanganate. Manganese oxide adheres to the surface and pores of the porous carbon, blocking the pores, resulting in low pore volume and specific surface area of the porous carbon material. The electrochemical performance is poor, and after multiple electrochemical cycles, manganese oxide will fall off the surface of the porous carbon, resulting in a large decrease in specific capacitance and poor cycle stability.
[0057] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A method for preparing porous carbon with high specific surface area and high conductivity, characterized in that: The preparation method is: Step A, adding N,N-dimethylformamide and alkali lignin into a flask, stirring and adding 1,4-di[(imidazole-4-carbonyl chloride)methyl]benzene and triethylamine, cooling after reaction, filtering, washing, and drying to obtain imidazole cross-linked modified alkali lignin; Step B, adding potassium permanganate aqueous solution to a flask, imidazole cross-linking modified alkali lignin, performing ultrasonic treatment in an ultrasonic instrument, filtering and drying the modified alkali lignin, placing it in an atmosphere furnace, passing nitrogen, and performing pyrolysis treatment; then passing water vapor to perform activation treatment; stopping passing water vapor, cooling to room temperature, and obtaining a porous carbon with high specific surface area and high conductivity.
2. The method for preparing porous carbon with high specific surface area and high conductivity according to claim 1, characterized in that: In the step A, the masses of 1,4-di[(imidazole-4-carbonyl chloride)methyl]benzene and triethylamine are 5-30% and 2.8-17% of the mass of alkali lignin, respectively.
3. The method for preparing porous carbon with high specific surface area and high conductivity according to claim 1, characterized in that: The reaction in step A is carried out at 70-90° C. for 12-24 hours.
4. The method for preparing porous carbon with high specific surface area and high conductivity according to claim 1, characterized in that: The mass concentration of the potassium permanganate solution in step B is (3-20) g / L.
5. The method for preparing porous carbon with high specific surface area and high conductivity according to claim 1, characterized in that: The frequency of the ultrasonic treatment in step B is 20-30 kHz, and the ultrasonic time is 2-4 hours.
6. The method for preparing porous carbon with high specific surface area and high conductivity according to claim 1, characterized in that: In the step B, the temperature of the pyrolysis treatment is 550-700° C., and the time is 1.5-2 h; the flow rate of the water vapor is 0.3-0.6 mL / L; and the temperature of the activation treatment is 800-900° C., and the time is 1-1.5 h.
7. The method for preparing porous carbon with high specific surface area and high conductivity according to claim 2, characterized in that: The preparation method of the 1,4-bis[(imidazole-4-carbonyl chloride)methyl]benzene is: Step (1), adding N, N-dimethylformamide and methyl imidazole-4-carboxylate into a flask, passing nitrogen, adding sodium hydride, heating to 80-90° C., reacting for 1-2 hours, then adding 1, 4-bis (bromomethyl) benzene, reacting for 18-24 hours, removing N, N-dimethylformamide by distillation under reduced pressure, adding the washed product to methanol, adding a sodium hydroxide solution having a mass concentration of 60-80 g / L, heating to 70-85° C., condensing and refluxing for 5-8 hours, removing methanol by distillation under reduced pressure, adding a hydrochloric acid solution to adjust the pH to 4-5, filtering, washing the filter cake, and obtaining 1, 4-bis [(imidazole-4-carboxylic acid) methyl] benzene; Step (2), add thionyl chloride and 1,4-di[(imidazole-4-carboxylic acid)methyl]benzene into a flask, introduce nitrogen, heat to 60-70° C., condense and reflux for 3-4 hours, distill under reduced pressure, and dry to obtain 1,4-di[(imidazole-4-carboxylic acid)methyl]benzene.
8. The method for preparing porous carbon with high specific surface area and high conductivity according to claim 7, characterized in that: In the step (1), the masses of methyl imidazole-4-carboxylate and sodium hydride are 96-106% and 28-34% of the mass of 1,4-di(bromomethyl)benzene, respectively.
9. The method for preparing porous carbon with high specific surface area and high conductivity according to claim 7, characterized in that: In the step (2), the mass of 1,4-di[(imidazole-4-carboxylic acid)methyl]benzene is 25-35% of the mass of thionyl chloride.
10. Use of the high specific surface area and high conductivity porous carbon obtained by the preparation method according to any one of claims 1 to 9 in supercapacitor electrode materials.
Citation Information
Patent Citations
A manganese dioxide composite nitrogen-sulfur dual-doped porous carbon, its preparation method and application
CN112820550B